2016
DOI: 10.1177/0954408915589687
|View full text |Cite
|
Sign up to set email alerts
|

Optimized bolt tightening procedure for different tightening strategies—FEA study

Abstract: This paper presents results of detailed nonlinear finite element analysis of gasketed bolted flange pipe joints of different sizes (1, 4, 5, 6, 8, 10, 20 in.) of 900# pressure class for achieving proper preload close to the target stress values with and without considering yielding at bolt and flange and gasket crushing recommended by ASME and industrial guidelines for optimized performance using customized optimization algorithm. In addition, two strategies torque control method and stretch control method are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Figure 1 shows the flowchart of MAK for optimization problems. 33,34 The algorithm works for both linear and nonlinear problems in statics and transient analysis. Initially, the algorithm takes a mesh as an input with boundary conditions and calls an appropriate solver (linear/nonlinear).…”
Section: Makmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flowchart of MAK for optimization problems. 33,34 The algorithm works for both linear and nonlinear problems in statics and transient analysis. Initially, the algorithm takes a mesh as an input with boundary conditions and calls an appropriate solver (linear/nonlinear).…”
Section: Makmentioning
confidence: 99%
“…In order to achieve more accurate results, Abid et al. 33,34 proposed a generalized optimization algorithm for GBFJs for both the ASME 35 and industrial guidelines 36 for different flange sizes and better accuracy was achieved compared to the manual and semiautomatic algorithms. However, it is realized that the accuracy of results can be further increased keeping in view the limitations of the generalized optimization algorithm for the required target stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of thermal loading has not been considered to date, due to its complexity of application during experimental studies. In addition, Abid et al and Fukuoka et al [4][5][6][7][8][9][10][11] in their numerical studies have concluded that gasketed joints show better sealing performance if bolts in a joint are tightened as per ASME bolt tightening strategy [12] as compared to the various accepted industrial practices [13].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, joint behavior of bolted flange joints are performed in various studies. [13][14][15][16][17][18][19][20][21][22] Most of these research focuses on the effect of sequence of bolt-tightening and loading of internal pressure only while the impact of combination of internal pressure, axial loading, and bending load, on the joint is observed to be limited. The impact of bending load in combination with internal pressure and axial load, is more important in case of the offshore heavy structures, and might contribute significantly in the catastrophic failure of the joint.…”
Section: Introductionmentioning
confidence: 99%